PERHITUNGAN HARGA POKOK PRODUKSI PADA UMKM BATIK CIBULUH KOTA BOGOR MENGGUNAKAN APLIKASI COSTMATE - Novitasari, Novitasari; Agha, Ridwan Zulfi; Fatimah, Hayati; Nuraeni, Yenni (Jurnal Abdi Insani, 2024)
Batik craftsmen in Cibuluh Batik Village, Bogor have not been able to analyze the production costs incurred, so that in calculating the cost of production they are not accurate. Inaccurate calculation of the cost of production of batik results in the determination of the selling price being inaccurate and uncompetitive in the market. With this problem, lecturers and students of the Accounting Expertise Field at the Accounting Department of the Jakarta State Polytechnic in partnership with the Cibuluh batik group held training and assistance in calculating the cost of production of batik. This activity is to increase the knowledge of Cibuluh batik craftsmen in the field of accounting and improve their skills in calculating the cost of production. In addition, providing assistance so that they can determine the selling price of batik correctly. The training began by providing basic cost accounting material, then an introduction to the CostMate application and a workshop on calculating the cost of production of batik using the CostMate application. The training ended with the collection of participant performance results on cases given during the training and filling out a training success questionnaire. The training was responded to very well by the participants. From the results of the performance assessment of the given case, all work groups have been able to complete the calculation of the cost of production using the CostMate application with accurate results and on time. And from the results of filling out the questionnaire, 100% of training participants stated that they were able to calculate the cost of batik production independently with the help of the CostMate application. All participants stated that the training held was interesting and useful to support their batik business. The training and mentoring of the cost of production carried out had a positive impact on increasing the competence and satisfaction of training participants. Training in calculating the cost of production with the CostMate application was able to improve the competence of participants in calculating the cost of production and the selling price of batik.